The Role of Aquaporins in the Kidney of Euryhaline Teleosts - Engelund, Morten B.; Madsen, Steffen (Frontiers in Physiology, 2011)
Water balance in teleost fish is maintained with contributions from the major osmoregulatory organs: intestine, gills and kidney. Overall water fluxes have been studied in all of these organs but not until recently has it become possible to approach the mechanisms of water transport at the molecular level. This mini-review addresses the role of the kidney in osmoregulation with special emphasis on euryhaline teleosts. After a short review of current knowledge of renal functional morphology and regulation, we turn the focus to recent molecular investigations of the role of aquaporins in water and solute transport in the teleost kidney. We conclude that there is much to be achieved in understanding water transport and its regulation in the teleost kidney and that effort should be put into systematic mapping of aquaporins to their tubular as well as cellular localization.